The success of think tanks in Turkey and the Czech Republic: A comparative analysis in the 10-year perspective - Sobotková, Lucie; Kulac, Onur (Univerzita Alexandru Ioan Cuza, 2020)
Along with global influences and changes brought by the ages, expectations and needs of citizens have multiplied in the vast majority of the world. For this reason, governments have to cope with problems in numerous policy areas. In this process, as unofficial public policy actors, think tanks undertake significant tasks in order to provide various policy alternatives and even solutions to governments. Therefore, the participation of think tanks in the policy-making process makes a crucial contribution to policy outputs. The number of think tanks, the policy areas in which they operate, and their global interactions are functional indicators of a country's level of development. The foremost aim of this paper is to put forth the worldwide success of think tanks in Turkey and the Czech Republic in a comparative manner. To this end, "Global Go To Think Tank Index Reports" (GGTTT Rankings) are taken as the starting point in order to conduct a 10-year perspective analysis with regards to domestic economy policies, international economy policies, education policies, foreign policies and international affairs, defence and national security policies, and university-affiliated think tanks. Furthermore, functional determinations and policy recommendations will be offered in a systematic way for the think tanks in both countries.
Úspěch think tanků v Turecku a v České republice: Komparativní analýza v desetileté perspektivě
Keywords: think tanks; public policy; participation; Turkey; Czech Republic; think tanks; veřejná politika; participace; Turecko; Česká republika